Arthroscopic Treatment of Capitate Nonunion: A New Technique - de Villeneuve Bargemon, Jean-Baptiste; Jaloux, Charlotte; Levet, Paul; Levadoux, Michel (Journal of Wrist Surgery, 2021)
Isolated fractures of the capitate are very rare which means that their nonunion is even rarer. Repair techniques have always been performed by open surgery which may result in loss of mobility due to the capsulotomy. The typically used surgical techniques such as arthrodesis of the carpal or wrist bones can have irreversible consequences on range of motion. No arthroscopic technique has ever been described for this condition. Here, we describe a case of isolated capitate nonunion without ligament tears or other carpal fractures in a 21-year-old male, following a capitate fracture 10 years prior. We describe our arthroscopic treatment technique for this capitate nonunion.
Keywords: wrist surgery; arthroscopy; capitate nonunion; bone graft